SISTEM PAKAR MENDETEKSI BIBIT SAPI UNGGUL DENGAN METODE CERTAINTY FACTOR - Friesky Christian Hendratama Jr.; Chairisni Lubis (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
The purpose of this research is to develop an application expert system detecting superior cow seedlings by detecting the type of cow using the characteristics that exist in cows, then based on the existing criteria, in the detection of the percentage value of accuracy for a cow can be a superior cow that produces superior cow seedlings. The characteristics and criteria are obtained from the results of interviews at the Mutiara Halim Trade Business and literature studies that have been conducted. The method used is the Certainty Factor method.The result obtained is an Expert System application that can be accessed by admins and users to detect the type and percentage value of superior seedlings in cows owned. The program is run by using XAMPP as Localhost and PHPMyAdmin as Database. Based on the trial using 40 original cow data that has been done, the results of species detection have an average accuracy percentage value of 99.9% and the result of the detection of superior cow seedlings has an average percentage value of 98.4%. Then it can be concluded that the system created can be run and can help the user in detecting the type and percentage of superior cow seedlings.